KELAYAKAN MEDIA BUKLET PADA MATERI KEANEKARAGAMAN HAYATI DI KELAS X SMA KECAMATAN SENGAH TEMILA - Hermawati, Yuni; Syamswisna, Syamswisna; Yokhebed, Yokhebed (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe purpose of this research was to know the feasibility of booklet media on biodiversity material in class X SMA Sengah Temila Subdistrict. Sengah Temila Subdistrict was one of the subdistricts located in Landak District of West Kalimantan Province, Indonesia. Maked this booklet media aimed to facilitate the learning process and facilitate learners in find examples of plants and facilitate in recognizing the useful plants that are in the environment. This booklet contains useful plants in Paloan Village, Sengah Temila Subdistrict, Landak District. The research was a qualitative descriptive method and the technique of data collection, such as observation, and documentation. Testing of the validity / feasibility of booklet media was done by two lecturers of Biology Education Faculty of Teacher Training and Education of Tanjungpura University, one of biology teacher at SMAN 1 Sengah Temila, one biology teacher at SMA Berkat Bagi Bangsa and one of biology teacher of SMA Harapan Pahuman. The booklet media validation is analyzed based on three aspects was a format, language, and content are valid with an average total validation of 0.99 on the Biodiversity material.Â Keywords : booklet, biodiversity, Sengah Temila SubdistrictÂ